Photoassisted High-Performance Lithium Anode Enabled by Oriented Crystal Planes - Bao, Weizhai; Wang, Ronghao; Qian, Chengfei; Li, Muhan; Sun, Kaiwen; Yu, Feng; Liu, He; Guo, Cong; Li, Jingfa (ACS nano, 2022)
Lithium (Li) metal anodes are candidates for the next-generation high-performance lithium-ion batteries (LIBs). However, uncontrolable Li dendrite growth leads to safety issues and a low Coulombic efficiency (CE), which hinders the commercialization of Li metal batteries. Stable Li anodes based on the tailored plane deposition and photoassisted synergistic current collectors are currently the subject of research; however, there are few related studies. To suppress the growth of Li dendrites and achieve dense Li deposition, we design a low-cost customized-facet/photoassisted synergistic dendrite-free anode. The tailored (002) plane endows it with a nanorod array/microsphere composite structure and exhibits a strong affinity for Li, which effectively reduces the Li+ nucleation overpotential and promotes uniform Li deposition. Notably, during the photoassisted Li deposition/stripping process, due to electron–hole separation, a weakly charged layer is formed on the (002) surface and local charge carrier changes are induced, reducing the overpotential by 8.3 mV, enhancing the reaction kinetics, and resulting in a high CE of ∼99.3% for the 300th cycle at 2 mA cm–2. This work is of great significance for the field of next-generation photoassisted Li metal anodes.